2017
DOI: 10.1016/j.cortex.2016.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Transient medial prefrontal perturbation reduces false memory formation

Abstract: Knowledge extracted across previous experiences, or schemas, benefit encoding and retention of congruent information. However, they can also reduce specificity and augment memory for semantically related, but false information. A demonstration of the latter is given by the Deese-Roediger-McDermott (DRM) paradigm, where the studying of words that fit a common semantic schema are found to induce false memories for words that are congruent with the given schema, but were not studied. The medial prefrontal cortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
22
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 90 publications
(112 reference statements)
9
22
2
Order By: Relevance
“…Recent studies that have reported on the memory modulation effect after applying mPFC stimulation in animals (Liu, Jain, Vyas, & Lim, 2015) and humans (Berkers et al, 2017) partly support the feasibility of our suggestion. Recent studies that have reported on the memory modulation effect after applying mPFC stimulation in animals (Liu, Jain, Vyas, & Lim, 2015) and humans (Berkers et al, 2017) partly support the feasibility of our suggestion.…”
Section: Implications For Future Clinical Applicationssupporting
confidence: 82%
See 1 more Smart Citation
“…Recent studies that have reported on the memory modulation effect after applying mPFC stimulation in animals (Liu, Jain, Vyas, & Lim, 2015) and humans (Berkers et al, 2017) partly support the feasibility of our suggestion. Recent studies that have reported on the memory modulation effect after applying mPFC stimulation in animals (Liu, Jain, Vyas, & Lim, 2015) and humans (Berkers et al, 2017) partly support the feasibility of our suggestion.…”
Section: Implications For Future Clinical Applicationssupporting
confidence: 82%
“…Considering the strong functional connections between the mPFC and other multiple memory-related brain areas in our MTLR patients with a normal memory function, we suggest that the mPFC could be a novel target for brain stimulation in people with MTL-dysfunctionrelated memory disturbance. Recent studies that have reported on the memory modulation effect after applying mPFC stimulation in animals (Liu, Jain, Vyas, & Lim, 2015) and humans (Berkers et al, 2017) partly support the feasibility of our suggestion.…”
Section: Implications For Future Clinical Applicationssupporting
confidence: 82%
“…sleep). The mPFC can be inhibited by continuous theta burst (cTBS) stimulation, leading to a reduction in false recall of critical lures (19), in line with studies on mPFC lesioned patients (18). Note however that these findings are related to knowledge structures in general and it remains to be investigated how these findings transfer to emotional memory.…”
Section: Introductionsupporting
confidence: 61%
“…These findings indicate the necessity of the mPFC for schematic memory formation. In support of the causal role of the mPFC in schema memory formation, a recent neurostimulation study (19) used transient magnetic stimulation (TMS) to perturb medial prefrontal processing before the performance of a Deese-Roedinger-McDermott (DRM) task (20). In this false memory task, participants are presented with lists of semantically related words (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation